2022
DOI: 10.1186/s12933-022-01564-y
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in insulin sensitivity and prevention of high fat diet-induced liver pathology using a CXCR2 antagonist

Abstract: Background Liver pathology (LP) characteristic of non-alcoholic fatty acid disease (NAFLD)/non-alcoholic steatohepatitis (NASH) is a prevalent co-morbidity of type 2 diabetes (T2D). Accumulating evidence indicates that neutrophils driving insulin resistance (IR), including hepatic IR, precipitate T2D-associated NAFLD/NASH. We hypothesized that targeting neutrophil accumulation into insulin-sensitive tissues in mice using a CXCR2 antagonist under T2D-precipitating high fat diet (HFD) could impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 86 publications
1
6
0
Order By: Relevance
“…The recruitment of neutrophils and the formation of NETs led to an impairment in liver repair in aged mice. Previous studies have reported that CXCR2 antagonists (eg, SB225002 and AZD5069) reduce neutrophil infiltration in the liver 42–44 . Based on our findings, targeting CXCL2 led to reduced recruitment of neutrophils by intrahepatic macrophages in aged mice.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The recruitment of neutrophils and the formation of NETs led to an impairment in liver repair in aged mice. Previous studies have reported that CXCR2 antagonists (eg, SB225002 and AZD5069) reduce neutrophil infiltration in the liver 42–44 . Based on our findings, targeting CXCL2 led to reduced recruitment of neutrophils by intrahepatic macrophages in aged mice.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have reported that CXCR2 antagonists (eg, SB225002 and AZD5069) reduce neutrophil infiltration in the liver. [42][43][44] Based on our findings, targeting CXCL2 led to reduced recruitment of neutrophils by intrahepatic macrophages in aged mice. Using an HIRI model, we confirmed that an anti-CXCL2 antibody effectively reduced neutrophil recruitment and NET formation, thereby significantly alleviating HIRI in the aged liver.…”
Section: Discussionmentioning
confidence: 67%
“…Based on the research reported [ 25 ], at the end of the experiment, all rats were decollated to death, and liver tissues were taken. The liver tissues were fixed in 4% neutral formaldehyde for 48 h, dehydrated in ethanol gradient, and embedded in paraffin wax to produce pathological sections of 3 μ m thickness.…”
Section: Methodsmentioning
confidence: 99%
“…AZD5069 is a small-molecule inhibitor of CXCR2. AZD5069 can significantly improve liver pathology in NAFLD, with reduced lipid content and hepatic neutrophil accumulation and improved insulin sensitivity[ 65 ]. In addition, AZD5069-mediated CXCR2 inhibition induces reprogramming of the tumor immune microenvironment, which promotes immune checkpoint inhibition in NASH-HCC[ 63 ], suggesting that blocking infiltrating neutrophil CXCR2 can restore sensitivity to immunotherapy in the NASH liver[ 66 ].…”
Section: Approaches Targeting the Inflammatory Pathway To Treat Nafld...mentioning
confidence: 99%